Associations Between Frailty and Inflammation, Physical, and Psycho-Social Health in Older Adults: A Systematic Review - Pothier, Kristell; Gana, Wassim; Bailly, Nathalie; Fougère, Bertrand (Frontiers in Psychology, 2022)
Frailty is a complex geriatric syndrome with multifactorial associated mechanisms that need to be more deeply examined to help reverse the adverse health-related outcomes. Specific inflammatory and physical health markers have been associated with the onset of frailty, but the associations between these factors and psycho-social health outcomes seem less studied. This systematic review aimed to identify, in the same study design, potential associations between frailty and markers of inflammation, and physical or psycho-social health. Literature search was performed from inception until March 2021 using Medline, Psychinfo and EMBASE. Three raters evaluated the articles and selected 22 studies, using inclusion and exclusion criteria (n = 17 373; 91.6% from community-dwelling samples). Regarding biomarkers, 95% of the included studies showed significant links between inflammation (especially higher levels of CRP and IL-6), and frailty status. 86% of the included studies showed strong links between physical health decline (such as lower levels of hemoglobin, presence of comorbidities, or lower physical performance), and frailty status. Only 13 studies among the 22 included ones evaluated psycho-social variables and mixed results were observed regarding the relationships with frailty. Results are discussed in terms of questioning the medical perception of global health, centering mostly on the physical dimension. Therefore, the development of future research studies involving a more exhaustive view of frailty and global (bio-psycho-social) health is strongly encouraged.